농작물 광 피해 방지를 위한 LED 조명 개발 및 생육 검증 - 조범연(Byoum-Youn Cho); 배은영(Eun-Young Bea); 김경상(Gyoung-Sang Kim); 조영태(Young-Tae Cho); 신오순(Oh-Soon Shin) (한국생산제조학회지, 2024)
This study aimed to develop LED(light emitting diode) lighting that has a minimal impact on crop growth. An LED light source was developed with a wavelength band of 550-620 nm, which does not affect photosynthesis in plants and has a PPF(photosynthetic photon flux) index of 1.0 μmol/m2/s or less, with a minimal impact on photosynthetic activity. Consequently, the light output distribution in the wavelength band of 550-620 nm was 83.1%, with a PPF index of 0.453 μmol/m2/s, which minimized the impact on crops. In addition, LED lighting with a color temperature free of heterogeneity was implemented. Therefore, the minimization of the light impact was verified through comparative experiments on the initial growth of the five crops. To verify the light pollution effects of LED lighting on the crop yield, empirical tests must be conducted until the crops are harvested. KCI Citation Count: 0